Heat transfer characteristics in forced convection through a rectangular channel with broken V-shaped rib roughened surface. (October 2015) - Fustinoni, D; Gramazio, P; Colombo, L; Niro, A
Abstract: In this paper we present experimental results for a rectangular channel with the lower and upper walls configured with V-shaped broken ribs pointing both upward and downward the flow stream, as well as in a mixed configuration. Results for V-shaped ribs upward pointing are also reported for comparison. The duct cross-section is 120-mm wide and 12-mm height; the rib- roughened walls are operated at fixed temperature whereas the channel side walls are adiabatic. The ribs have square cross section of 2 mm in side, a V-apex angle of 60°, and a pitch-to-side ratios of 10 and 40. Reynolds number has been varied between 700 and 7500. The results show that the flow regime seems to be turbulent even at the lowest tested value of Re, and the friction factor is quite independent of Re, i.e., the typical trend for k-roughened surfaces. Broken and continued ribs seems to perform with no evident differences between them, except at the lowest values of Re while prevailing the former or the latter according to p/e . Anyway, adopting ribbed surface is always advantageous and allows a maximum heat transfer enhancement factor of 4.9.